2007
DOI: 10.1111/j.1439-0442.2007.00850.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Various Degrees of Dystocia in Dairy Cattle on Calf Viability, Milk Production, Fertility and Culling

Abstract: The objective of this study was to analyse the effect of dystocia on calf viability, milk production, fertility and culling under field (farm) conditions in a retrospective case-control study. A total of 253 calvings that were attended by a veterinarian were classified into three categories: mild dystocia (MD), severe dystocia (SD) and caesarean section (CS). For every case of dystocia, a control was chosen from the same farm and matched for calving month, breed and parity. Cases and controls were compared con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 22 publications
5
62
0
4
Order By: Relevance
“…Dystocia, defined as a prolonged or difficult parturition, affects the profitability of herds, animal welfare, and acceptability of the production system by the consumer (Carnier et al, 2000). Not only does calving difficulty increase farm workload, it also has adverse effects on the subsequent survival, health, and performance of mothers and offspring (Dematawewa and Berger, 1997;Lombard et al, 2007;Tenhagen et al, 2007;Barrier and Haskell 2011). Calving difficulty impaired milk production of dairy cows in terms of cow's milk production and saleable milk yields, highlighting impaired income for dairy producers as well as detrimental effects on the productivity of the cows (Barrier and Haskell, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Dystocia, defined as a prolonged or difficult parturition, affects the profitability of herds, animal welfare, and acceptability of the production system by the consumer (Carnier et al, 2000). Not only does calving difficulty increase farm workload, it also has adverse effects on the subsequent survival, health, and performance of mothers and offspring (Dematawewa and Berger, 1997;Lombard et al, 2007;Tenhagen et al, 2007;Barrier and Haskell 2011). Calving difficulty impaired milk production of dairy cows in terms of cow's milk production and saleable milk yields, highlighting impaired income for dairy producers as well as detrimental effects on the productivity of the cows (Barrier and Haskell, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Even beyond those 48 hr, cows that have experienced dystocia are more likely to die or be culled in early lactation and over the lactating period (Dematawewa & Berger, 1997;Tenhagen et al, 2007;López de Maturana et al, 2007b;De Vries et al, 2010). Furthermore, the fear that the animal might experience difficulty at her next parturition may increase weight to the farmer's decision to cull a dystocial cow.…”
Section: Dystociamentioning
confidence: 99%
“…In fact, although some authors seem to find a deleterious effect on the overall lactation of cows (Dematawewa & Berger, 1997;, some studies have suggested that these effects disappear beyond 14 days in milk (DIM) (Rajala & Gröhn, 1998), 90 DIM (Thompson et al, 1983) or six month postpartum (Tenhagen et al, 2007). Furthermore, the degree of difficulty from which milk losses are reported ranges from slight degrees of diff iculty (Dematawewa & Berger, 1997) up to only in severe cases when surgery is needed (Tenhagen et al, 2007). Additionally, the magnitude of losses has been suggested to be greater with increasing degrees of difficulty (Dematawewa & Berger, 1997).…”
Section: Dystociamentioning
confidence: 99%
“…In agreement with Murray et al [16], calves born from a hard pull were at greater risk of reduced vigor compared to calves born from an easy pull or observed but unassisted at calving. Newborn calves experiencing reduced vigor due to trauma at birth may be at increased risk of stillbirth or have long-term consequences to health and productivity [4,30,31]. As such, it is important to minimize these consequences in the newborn calf with intervention strategies following calving.…”
Section: Discussionmentioning
confidence: 99%